Development of Integrated Logistics Paradigm in Solving Complex Multi-Criteria Problems of Material Flow Management - Trifonov, Pavel V.; Seryshev, Roman V. (International Journal of Supply Chain Management, 2020)
The paper considers the historical retrospective of the development of logistics paradigms and analyzes the apparatus used to solve applied logistics problems. Obstacles to the implementation of the integrated paradigm of logistics, its analytical approach and simulation tools are investigated, which allowed to determine the structure of the decision support system in the management of material flow and formulate the concept of logistics coordination. As a result, it was possible to develop a conceptual scheme of the economic mechanism of logistics coordination of the production enterprise and to form a General algorithm for mathematical modeling of simulation and analytical models of logistics coordination and solving complex problems of material flow management in complex organizational and technical systems.